Chromophore Induced Effects in Iron(III) Complexes - Schmitz, Lennart; Argüello Cordero, Miguel A.; Al-Marri, Mohammed J.; Schoch, Roland; Egold, Hans; Neuba, Adam; Steube, Jakob; Bracht, Bastian Johannes; Bokareva, Olga S.; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
In the search for noble metal free photocatalytic systems, iron is the dream candidate. To increase excited state lifetimes of iron complexes, the multichromophoric approach is promising, combining organic chromophores with photoactive iron complexes, potentially enabling a reservoir effect. We present a series of chromophore-functionalized complexes based on the parental FeIII complex [Fe(ImP)2][PF6] (HImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)). The four organic chromophores benzene, naphthalene, anthracene, and pyrene are attached to the ImP-ligand in para-position to the coordination site to systematically investigate the influence of the steric demand and electronic properties of the chromophore on charge transfer lifetimes as well as photodynamics. A thorough ground state characterization was conducted in addition to investigations of the excited state dynamics by transient absorption spectroscopy and streak camera emission measurements. The conclusions drawn are supported by extensive DFT calculations. The emission coefficients could be significantly improved by the addition of chromophores. After excitation of the complexes with larger chromophores, coplanarization of the backbone and complex motif occurs to stabilize the formal charge. This results in population of a superligand state that exhibits a much faster radiationless relaxation to the ground state compared to the parent complex, hindering a reservoir effect.
Keywords: Photo

Water Sorption on Isoreticular CPO-27-Type MOFs: From Discrete Sorption Sites to Water-Bridge-Mediated Pore Condensation - Kloß, Marvin; Schäfers, Lara; Zhao, Zhenyu; Weinberger, Christian; Egold, Hans; Tiemann, Michael (Nanomaterials)
Pore engineering is commonly used to alter the properties of metal–organic frameworks. This is achieved by incorporating different linker molecules (L) into the structure, generating isoreticular frameworks. CPO-27, also named MOF-74, is a prototypical material for this approach, offering the potential to modify the size of its one-dimensional pore channels and the hydrophobicity of pore walls using various linker ligands during synthesis. Thermal activation of these materials yields accessible open metal sites (i.e., under-coordinated metal centers) at the pore walls, thus acting as strong primary binding sites for guest molecules, including water. We study the effect of the pore size and linker hydrophobicity within a series of Ni2+-based isoreticular frameworks (i.e., Ni2L, L = dhtp, dhip, dondc, bpp, bpm, tpp), analyzing their water sorption behavior and the water interactions in the confined pore space. For this purpose, we apply water vapor sorption analysis and Fourier transform infrared spectroscopy. In addition, defect degrees of all compounds are determined by thermogravimetric analysis and solution 1H nuclear magnetic resonance spectroscopy. We find that larger defect degrees affect the preferential sorption sites in Ni2dhtp, while no such indication is found for the other materials in our study. Instead, strong evidence is found for the formation of water bridges/chains between coordinating water molecules, as previously observed for hydrophobic porous carbons and mesoporous silica. This suggests similar sorption energies for additional water molecules in materials with larger pore sizes after saturation of the primary binding sites, resulting in more bulk-like water arrangements. Consequently, the sorption mechanism is driven by classical pore condensation through H-bonding anchor sites instead of sorption at discrete sites.

Isostructural Series of a Cyclometalated Iron Complex in Three Oxidation States - Steube, Jakob; Fritsch, Lorena; Kruse, Ayla; Bokareva, Olga S.; Demeshko, Serhiy; Elgabarty, Hossam; Schoch, Roland; Alaraby, Mohammad; Egold, Hans; Bracht, Bastian Johannes; Schmitz, Lennart; Hohloch, Stephan; et al. (Inorganic Chemistry)
An isostructural series of FeII, FeIII, and Fe(IV)complexes [Fe(ImP)2]0/+/2+ utilizing the ImP 1,1′-(1,3-phenylene)-bis(3-methyl-1-imidazol-2-ylidene) ligand, combining N-heterocy-clic carbenes and cyclometalating functions, is presented. The strong donor motif stabilizes the high-valent Fe(IV) oxidation state yet keeps the FeII oxidation state accessible from the parent Fe(III)compound. Chemical oxidation of [Fe(ImP)2]+ yields stable [FeIV(ImP)2]2+. In contrast, [FeII(ImP)2]0, obtained by reduction,is highly sensitive toward oxygen. Exhaustive ground state characterization by single-crystal X-ray diffraction, 1H NMR,Mössbauer spectroscopy, temperature-dependent magnetic measurements, a combination of X-ray absorption near edge structureand valence-to-core, as well as core-to-core X-ray emission spectroscopy, complemented by detailed density functional theory (DFT) analysis, reveals that the three complexes[Fe(ImP)2]0/+/2+ can be unequivocally attributed to low-spin d6, d5, and d4 complexes. The excited state landscape of the Fe(II) and Fe(IV) complexes is characterized by short-lived 3MLCT and 3LMCT states, with lifetimes of 5.1 and 1.4 ps, respectively. In the FeII-compound, an energetically low-lying MC state leads to fast deactivation of the MLCT state. The distorted square-pyramidal state, where one carbene is dissociated, can not only relax into the ground state, but also into a singlet dissociated state. Its formation was investigated with time-dependent optical spectroscopy, while insights into its structure were gained by NMR spectroscopy.
Keywords: Photo

Iron(III)-Complexes with N-Phenylpyrazole-Based Ligands - Hirschhausen, Tanja; Fritsch, Lorena; Lux, Franziska; Steube, Jakob; Schoch, Roland; Neuba, Adam; Egold, Hans; Bauer, Matthias (Inorganics)
The use of iron as a replacement for noble metals in photochemical and photophysical applications is challenging due to the typically fast deactivation of short-lived catalytically active states. Recent success of a cyclometalated iron(III) complex utilizing a bis-tridentate ligand motif inspired the use of phenyl-1H-pyrazole as a bidentate ligand. Five complexes using the tris(1-phenylpyrazolato-N,C2)iron(III) complex scaffold are presented. In addition to the parent complex, four derivatives with functionalization in the meta-position of the phenyl ring are thoroughly investigated by single crystal diffractometry, UV-Vis-spectroscopy, and cyclic voltammetry. Advanced X-ray spectroscopy in the form of X-ray absorption and emission spectroscopy allows unique insights into the electronic structure as well as DFT calculations. The ligand design leads to overlapping MLCT and LMCT absorption bands, and emissive behavior is suppressed by low-lying MC states.
Keywords: Photo